Optimal growth as function of Re (A=1,Wo=25) - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesingleTG_Re_Wo25.dat extquotesingle shows the dependence of the maximum energy amplification on the Reynolds numbers at Womersley number of 25 and pulsation amplitude of 1. This file includes two columns: the first column indicates the Reynolds number; the second column indicates the maximum energy amplifiation.